2019
DOI: 10.1111/tme.12616
|View full text |Cite
|
Sign up to set email alerts
|

Human errors in manual techniques for ABO/D grouping are associated with potentially lethal outcomes

Abstract: Aims/Objectives:To review if ABO/D grouping errors are more likely to occur with manual intervention compared to automation.Background: Human errors in manual pre-transfusion testing may result in ABO/D-incompatible transfusions and catastrophic outcomes. Accurate ABO/D grouping is a critical part of pre-transfusion testing. Methods:This was a retrospective analysis of reports made to Serious Hazards of Transfusion (SHOT) between January 2004 and December 2016 where ABO/D grouping errors led to the transfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…[25][26][27][28][29][30][31] Moreover, WBIT is more likely to occur among mislabeled samples, which emphasizes the need for laboratories to reject patient samples with even minor labeling errors to reduce the risk of ABO-incompatible RBC transfusions. 20 Finally, Mistry et al 32 analyzed laboratory techniques reported in SHOT data from 2004 to 2016, and found that manual intervention was the cause of nearly all (93%) ABO/D typing errors; in contrast, there were no errors when full automation was used. The authors concluded that where manual testing cannot be avoided, results should be confirmed by automated techniques as soon as possible, and a backup process should be available at all times.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29][30][31] Moreover, WBIT is more likely to occur among mislabeled samples, which emphasizes the need for laboratories to reject patient samples with even minor labeling errors to reduce the risk of ABO-incompatible RBC transfusions. 20 Finally, Mistry et al 32 analyzed laboratory techniques reported in SHOT data from 2004 to 2016, and found that manual intervention was the cause of nearly all (93%) ABO/D typing errors; in contrast, there were no errors when full automation was used. The authors concluded that where manual testing cannot be avoided, results should be confirmed by automated techniques as soon as possible, and a backup process should be available at all times.…”
Section: Discussionmentioning
confidence: 99%
“…First, we consider the human factors involved [ 22 ]. We explored the reasons why Nurse A believed that the blood bag in her hand belonged to Patient X and not to Patient Y.…”
Section: Missed Opportunitiesmentioning
confidence: 99%
“…Human behavior is the result of a combination of human and environmental [20] or the SHELL model [21]. Figure 1 First, we consider the human factors involved [22]. We explored the reasons why Nurse A believed that the blood bag in her hand belonged to Patient X and not to Patient Y.…”
Section: Missed Opportunitiesmentioning
confidence: 99%
“…Errors can be reduced by eliminating human interventions. The introduction of fully automated systems in the laboratory resulted in reduction in errors compared to manual techniques (Mistry et al , ) and is a recommended standard (Chaffe et al , ). There is now good evidence that expanding electronic identification systems (EIS) for the full vein‐to‐vein (V2V) transfusion process also improves safety and reduces human error (Dzik et al , ; Murphy & Kay, ; Callum et al , ; Kaufman et al , ).…”
Section: Serious Pathological Complications Of Transfusion — Can Theymentioning
confidence: 99%